2013
DOI: 10.1007/s00592-013-0470-1
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, impaired vision and social role in people with diabetes: a multicenter observational study

Abstract: Diabetic retinopathy may induce visual impairment. We evaluated vision-related quality-of-life in patients with retinopathy and visual acuity <5/10 in the better eye using the 25-item National Eye

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 23 publications
3
24
0
4
Order By: Relevance
“…These negative feelings may have negative effects on patient reported outcome [14,19]. Vision loss due to diabetes can also affect the person's perception of their ability to function independently [20]. Therefore, it is of outmost importance to target the early stages of DRP to inhibit its progression, to prevent the disease from reaching a level that has severe impact on a person's quality of life [21,22].…”
Section: Patient Reported Outcomesmentioning
confidence: 99%
“…These negative feelings may have negative effects on patient reported outcome [14,19]. Vision loss due to diabetes can also affect the person's perception of their ability to function independently [20]. Therefore, it is of outmost importance to target the early stages of DRP to inhibit its progression, to prevent the disease from reaching a level that has severe impact on a person's quality of life [21,22].…”
Section: Patient Reported Outcomesmentioning
confidence: 99%
“…Studies also demonstrated that DR was the leading cause of new cases of blindness among adults aged 20-74 years [11] and severely influenced the quality of life in diabetic patients [12]. Previous studies have indicated that DR is more prevalent in patients at an earlier diagnosis Managed by Antonio Secchi.…”
Section: Introductionmentioning
confidence: 97%
“…Trento M et al in their multi-centered study in Italy also alluded that vision loss and ICV resulting in poor vision functioning, would impact on their social role and quality of life [6]. …”
Section: Introductionmentioning
confidence: 99%